The Effect of Prenatal Yoga on Life Satisfaction and Labour Self Efficacy in Women - Yolanda Mayraissa Tristanti Tristanti; Koekoeh Hardjito; Finta Isti Kundarti (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
Around 10% of pregnant women in the world experience anxiety symptoms. Self efficacy contributes the most to anxiety symptoms. Self efficacy in the face of childbirth is one of the factors that play an important role in fighting the fear of childbirth. Fear of childbirth has a negative impact on the life satisfaction of pregnant women. This study aims to analyse the effect of prenatal yoga on life satisfaction and childbirth self-efficacy in pregnant women. The method in this study is Quasi Experimental Design with pretest-posttest control group design. This research was conducted in the Working Area of Puskesmas Mrican and Puskesmas Sukorame Kediri City. The research sample amounted to 40 respondents who were divided into two groups taken randomly. From the results of the Wilcoxon sign rank test in the intervention group life satisfaction and childbirth self-efficacy showed a p-value of 0.000. In the control group life satisfaction showed a p-value of 0.012 and self efficacy showed a p-value of 0.041. The results of the Mann-Whitney Test on life satisfaction in both groups showed a p-value of 0.049, while self efficacy in both groups showed a p-value of 0.004. It can be concluded that both groups show significant results, namely there is an effect of prenatal yoga on life satisfaction and childbirth self-efficacy and from both groups show significant results, namely there are differences between the two groups in pregnant women.